2017
DOI: 10.1159/000478903
|View full text |Cite
|
Sign up to set email alerts
|

Lymphopenia and CD4+/CD8+ Cell Reduction under Fumaric Acid Esters

Abstract: Background: Fumaric acid esters (FAEs) are a broadly used therapy option for patients suffering from moderate-to-severe plaque psoriasis. Various studies in psoriasis have already shown peripheral blood lymphopenia during oral FAE therapy. Smaller studies also documented a reduction of CD4+ and CD8+ cell counts. Up to now, there are few case reports on opportunistic infections under FAE therapy - all of them associated with lymphopenia. Objective: To examine the influence of FAEs on white blood cells with spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 34 publications
6
19
1
1
Order By: Relevance
“…49 Usually, these phenomena are transient and reversible 14,[50][51][52] and may serve as a biomarker for drug efficacy of FAEs. 53 The changes in leucocyte and lymphocyte counts observed in the present study (Table 7) compare well with those recently reported by Sondermann et al 54 In that study, which included a much smaller cohort of 105 patients with psoriasis, the median leucocyte count decreased by about 17.3% and the median lymphocyte count by about 35.8% in the first 6 months of FAE therapy. Over a maximum FAE treatment period of 112 months, that group observed severe lymphopenia (CTCAE grade 3 or 4) in 11.4% of patients.…”
Section: Safety Aspectssupporting
confidence: 92%
See 4 more Smart Citations
“…49 Usually, these phenomena are transient and reversible 14,[50][51][52] and may serve as a biomarker for drug efficacy of FAEs. 53 The changes in leucocyte and lymphocyte counts observed in the present study (Table 7) compare well with those recently reported by Sondermann et al 54 In that study, which included a much smaller cohort of 105 patients with psoriasis, the median leucocyte count decreased by about 17.3% and the median lymphocyte count by about 35.8% in the first 6 months of FAE therapy. Over a maximum FAE treatment period of 112 months, that group observed severe lymphopenia (CTCAE grade 3 or 4) in 11.4% of patients.…”
Section: Safety Aspectssupporting
confidence: 92%
“…Over a maximum FAE treatment period of 112 months, that group observed severe lymphopenia (CTCAE grade 3 or 4) in 11.4% of patients. Although severe, persistent leucopenia and lymphopenia events were rare, these AEs resulted relatively often in the physician's decision to discontinue treatment to decrease the risk of opportunistic infection . Although opportunistic infections are very rare, 19 cases of progressive multifocal leucoencephalopathy have been identified among patients treated with different FAE preparations to date; 14 of these occurred during therapy for psoriasis (11 patients used Fumaderm ® and three patients used Psorinovo ® , DMF, compounding pharmacy).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations